2014
DOI: 10.1021/jz501536a
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Spectra and Stokes Shift Measurements of Single Organic Dyes at Room Temperature

Abstract: We report measurements of excitation and emission spectra of single, polymer-embedded, perylene dye molecules at room temperature. From these measurements, we can derive the Stokes shift for each single molecule. We determined the distribution of excitation and emission peak energies and, thus, the distribution of single molecule Stokes shifts. Single molecule Stokes shifts have not been recorded to date, and the Stokes shift has often been assumed to be constant in single molecule studies. Our data show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 36 publications
(52 reference statements)
1
21
0
Order By: Relevance
“…Previously, Stopel et al . 26 determined the Stokes shift of individual molecules recording both excitation and emission spectrum at room temperature. Against the general believe, they found that the Stokes shift varies between individual molecules.…”
mentioning
confidence: 99%
“…Previously, Stopel et al . 26 determined the Stokes shift of individual molecules recording both excitation and emission spectrum at room temperature. Against the general believe, they found that the Stokes shift varies between individual molecules.…”
mentioning
confidence: 99%
“…The experimentally determined Stokes shifts formed a broad distribution. 19 In the most recent study by Piatkowski et al, excitation spectra were acquired for about two minutes by a broadband Fourier approach. 20 The method's advantage is the robustness against blinking and bleaching of the observed molecule.…”
mentioning
confidence: 99%
“…which shows that the stokes shift value of PLM was considerably higher than that of polymer embedded organic dyes like perylene having stokes shift of 50 nm [30] .…”
Section: Analysis Of Photoluminescent Behaviour Of the Plm Comacromermentioning
confidence: 85%